Cervical cancer incidence in British Columbia: Predicting effects of changes from Pap to human papillomavirus screening and of changes in screening participation. (December 2017) - Coldman, Andrew; van Niekerk, Dirk; Smith, Laurie; Ogilvie, Gina
Objectives: To estimate the impact of increased participation in screening, and of the proposed change from Pap to human papillomavirus screening on the incidence of cervical cancer in British Columbia. Methods: For invasive cervical cancer cases diagnosed in British Columbia between 2002 and 2011, data were extracted on age and cancer morphology from the British Columbia Cancer Registry, and Pap screening history was obtained from the British Columbia Cervical Cancer Screening Program database. Only screening performed two to seven years prior to diagnosis was assumed to reduce subsequent risk of cancer. Results from randomized trials of human papillomavirus versus cytology screening and population based estimates of cytology screening were used to estimate the effect of a change in screening test and increases in participation. Results: Between 2002 and 2011, there were 1663 cases of cervical cancer reported; 660 (367 squamous and 293 non-squamous) were eligible and screened two to seven years prior to diagnosis. The predicted reduction by changing to human papillomavirus screening was 363 (95% confidence interval = 124–496) representing 22% of all cases. If 50% of subjects not screened two to seven years prior had undergone Pap screening, it is projected that a further 268 cases (16%) could have been prevented; if they had undergone human papillomavirus screening, a further 365 cases (22%) could have been prevented. Conclusions: For many women who develop cervical cancer, primary human papillomavirus testing could have substantially reduced their cancer risk. Human papillomavirus rather than Pap testing would further increase the gains from any increases in population screening participation.